Analisis Meta Teknik Grafting dalam Rhinoplasty: Evaluasi terhadap Hasil Estetika dan Komplikasi - Christanto, Antonius (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effectiveness of various grafting techniques in rhinoplasty procedures, particularly in relation to aesthetic outcomes and postoperative complications. Utilizing a systematic meta-analytical approach in this research reviewed 22 relevant scientific publications from leading databases, including PubMed and ScienceDirect. The analysis focused on the use of autologous, alloplastic, and acellular dermal grafts, as well as combined techniques such as diced cartilage wrapped in fascia (DC-F). Findings indicate that autologous grafts—particularly septal and auricular cartilage—offer superior structural stability and the highest patient satisfaction, with a low complication rate (<5%). Acellular dermal grafts and DC-F techniques were effective in revision cases, while alloplastic grafts showed a higher complication rate, including extrusion and infection. Spreader graft techniques also demonstrated improvement in postoperative nasal function. The discussion highlights the critical importance of selecting grafting techniques based on the patient’s anatomical condition and individualized needs. Autologous grafts remain the gold standard in primary rhinoplasty, while combination techniques provide effective solutions for complex cases. In conclusion, the success of rhinoplasty strongly depends on choosing the appropriate grafting method, with thorough consideration of aesthetic goals, functional outcomes, and complication risks.